A Cryogenic Hydrogen Ribbon for Laser Driven Proton Acceleration at Hz-Level Repetition Rate - Chagovets, T.; Viswanathan, J.; Tryus, M.; Grepl, F.; Velyhan, A.; Stancek, S.; Giuffrida, L.; Schillaci, F.; Cupal, J.; Koubikova, L.; Garcia, D.; Manzagol, J.; et al. (Frontiers in Physics, 2022)
We report on recent progress in deploying a continuous solid hydrogen ribbon as a debris-free and renewable laser-driven source of pure proton beams generated by a 30-fs laser with 1-J energy focused on the target at intensities 1019 W/cm2 and repetition rates up to 3.3 Hz. The stability of the ribbon position versus the laser interaction point and maximum repetition rate are addressed. Reliable acceleration of protons with cut-off energies up to 1.5 MeV is demonstrated using a 100-μm thick hydrogen target. The laser-target geometry presented demonstrates a robust experimental technique, which enables the operation of a laser–plasma source at Hz-level repetition rate.